Comparison of Quizizz and Animated Video Educational Methods Regarding Knowledge of the Dangers of Premarital Sex Among Adolescents Aged 15–18 at SMK PGRI 1, Kediri City - Marrizka Mutiara Islami; Ririn Indriani; Dwi Estuning Rahayu; Sumy Dwi Antono (Jurnal Kebidanan Manna, 2026)
Introduction: Premarital sexual behavior among adolescents remains a serious reproductive health problem in Indonesia, partly caused by a lack of knowledge about the dangers of free sex. Technology-based learning innovations suited to adolescent characteristics, such as Quizizz and animated video, are needed. This study aimed to analyze the difference in effectiveness between these two media in improving knowledge among adolescents aged 15–18 years at SMK PGRI 1 Kediri City. Methods: A quantitative quasi-experimental design with a Nonequivalent Control Group Design was used. A sample of 126 grade XI students was divided into a Quizizz group (Visual Communication Design department, 63 respondents) and an animated video group (Computer and Network Engineering department, 63 respondents) using cluster random sampling. Data were analyzed using the Wilcoxon Signed Rank Test and Mann-Whitney U Test. Results: The Wilcoxon test for the Quizizz group showed p=0.089 (not significant), while the animated video group showed p=0.000 (significant). The Mann-Whitney test showed p=0.000, with a higher mean rank for the animated video group (76.53) than Quizizz (50.47), indicating that animated video was more effective. Discussion: Animated video is more effective because visual and audio delivery of material is easier for adolescents to understand, while Quizizz tends to function as an evaluation medium, making it less optimal for improving knowledge. Conclusion: Animated video was proven more effective than Quizizz in improving knowledge among adolescents aged 15–18 years about the dangers of free sex, so this medium can be recommended as a reproductive health education method more suitable for adolescent characteristics.